TINDAK TUTUR EKSPRESIF PADA ACARA JEJAK ISLAM DI TVRI JAMBI BULAN APRIL-AGUSTUS 2023 (KAJIAN PRAGMATIK) - Desi, Desi; Amral, Sainil; Wahyuni, Uli (Universitas Batanghari, 2024)
This research aims to analyze the function of expressive speech acts in the speaker's speech on the Jejak Islam program on TVRI Jambi in April-August 2023. The analysis of this research will answer the research questions and the aim of this research, namely, to describe the function of expressive speech acts which include the function of praising, the function of complaining, the function of saying thank you, and the function of criticizing. This research will illustrate how speakers express the function of speech according to the context as a pragmatic study. The research method used to collect and analyze research data, researchers used qualitative descriptive methods. By using this research method researchers can describe the use of expressive speech acts from the four functions studied. With this method, researchers can describe the results of research on how speakers express themselves in praising, complaining, saying thank you, and criticizing in a speech. The results of this research can be explained that speakers on the jejak Islam program on TVRI Jambi in April-August 2023 were more likely to say that speech acts functioned to praise the activity. This can be seen from the dominant quotations that the researchers found for expressive speech with the function of praising, namely 43 quotations. For quotes that serve to criticize, the researchers only found 7 quotes. For expressive speech that functions to say thank you, researchers found 16 quotes. There were 12 quotations for the function of complaining. Thus, overall the researcher found 78 quotations for the four functions of expressive speech acts in this event program